Sustained activation of autophagy suppresses adipocyte maturation via a lipolysis-dependent mechanism. Issue 9 (1st September 2020) - Zhang, Xing; Wu, Dandan; Wang, Chunqing; Luo, Yan; Ding, Xiaofeng; Yang, Xin; Silva, Floyd; Arenas, Sara; Weaver, John Michael; Mandell, Michael; Deretic, Vojo; Liu, Meilian
ABSTRACT: Dysregulation of macroautophagy/autophagy is implicated in obesity and insulin resistance. However, it remains poorly defined how autophagy regulates adipocyte development. Using adipose-specific rptor/raptor knockout (KO), atg7 KO and atg7 rptor double-KO mice, we show that inhibiting MTORC1 by RPTOR deficiency led to autophagic sequestration of lipid droplets, formation of LD-containing lysosomes, and elevation of basal and isoproterenol-induced lipolysis in vivo and in primary adipocytes. Despite normal differentiation at an early phase, progressive degradation and shrinkage of cellular LDs and downregulation of adipogenic markers PPARG and PLIN1 occurred in terminal differentiation of rptor KO adipocytes, which was rescued by inhibiting lipolysis or lysosome. In contrast, inactivating autophagy by depletion of ATG7 protected adipocytes against RPTOR deficiency-induced formation of LD-containing lysosomes, LD degradation, and downregulation of adipogenic markers in vitro . Ultimately, atg7 rptor double-KO mice displayed decreased lipolysis, restored adipose tissue development, and upregulated thermogenic gene expression in brown and inguinal adipose tissue compared to RPTOR-deficient mice in vivo . Collectively, our study demonstrates that autophagy plays an important role in regulating adipocyte maturation via a lipophagy and lipolysis-dependent mechanism. Abbreviations: ATG7: autophagy related 7; BAT: brown adipose tissue; CEBPB/C/EBPβ: CCAAT enhancer binding protein beta; DGAT1: diacylglycerol O-acyltransferase 1; eWAT: epididymal white adipose tissue; iWAT: inguinal white adipose tissue; KO: knockout; LD: lipid droplet; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MTOR: mechanistic target of rapamycin kinase; MTORC1: mechanistic target of rapamycin kinase complex 1; PLIN1: perepilin 1; PNPLA2/ATGL: patatin-like phospholipase domain containing 2; PPARG/PPARγ: peroxisome proliferator activated receptor gamma; RPTOR: regulatory associated protein of MTOR complex1; TG: triglyceride; ULK1: unc-51 like kinase 1; UCP1: uncoupling protein 1; WAT: white adipose tissue